2017
DOI: 10.1186/s13229-017-0166-4
|View full text |Cite
|
Sign up to set email alerts
|

Testing the excitation/inhibition imbalance hypothesis in a mouse model of the autism spectrum disorder: in vivo neurospectroscopy and molecular evidence for regional phenotypes

Abstract: BackgroundExcitation/inhibition (E/I) imbalance remains a widely discussed hypothesis in autism spectrum disorders (ASD). The presence of such an imbalance may potentially define a therapeutic target for the treatment of cognitive disabilities related to this pathology. Consequently, the study of monogenic disorders related to autism, such as neurofibromatosis type 1 (NF1), represents a promising approach to isolate mechanisms underlying ASD-related cognitive disabilities. However, the NF1 mouse model showed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 28 publications
(60 reference statements)
6
54
0
Order By: Relevance
“…One study reported a correlation between GABA concentration in the visual cortex (VC) and the degree of perceptual suppression during binocular rivalry in adolescents with typical development, whereas the correlation was significantly lower in autistic patients 20 . Another study reported increased cortical and striatal GABA/glutamate ratios in a neurofibromatosis type 1 mouse model of autism 21 . Hence, the main aim of the current study using MRS is to determine whether bumetanide could regulate GABA/glutamate ratio in the brain and reduce the severity of the autistic symptoms in young children with ASD.…”
Section: Introductionmentioning
confidence: 97%
“…One study reported a correlation between GABA concentration in the visual cortex (VC) and the degree of perceptual suppression during binocular rivalry in adolescents with typical development, whereas the correlation was significantly lower in autistic patients 20 . Another study reported increased cortical and striatal GABA/glutamate ratios in a neurofibromatosis type 1 mouse model of autism 21 . Hence, the main aim of the current study using MRS is to determine whether bumetanide could regulate GABA/glutamate ratio in the brain and reduce the severity of the autistic symptoms in young children with ASD.…”
Section: Introductionmentioning
confidence: 97%
“…Histological studies have suggested several potential cellular substrates associated to connectome miswiring of autism including altered cortical lamination [76][77][78][79] and columnar layout 80,81 , together with atypical neuronal migration that can result in cortical blurring 77,82 and changes in spine density of cortical projection neurons 83,84 . Such cellular changes likely impact on the functional organization of cortical microcircuits in autism, also suggested by molecular studies in animals 4,[22][23][24][25]85,86 . These findings collectively support the imbalance in excitation and inhibition of cortical areas in autism 4,9,16,22,87,88 , which have been related to anomalies in cortical neurotransmitter systems [89][90][91][92] and atypical subcortico-cortical interactions with subcortical structures such as thalamus modulating this balance 7,11,24,74,75,93 .…”
Section: Discussionmentioning
confidence: 80%
“…Magnetic resonance spectroscopy (MRS) is an in vivo tool capable of non-invasively measuring brain metabolites. Only the MCRI site will acquire two GABA-edited magnetic resonance spectra using the localised spectroscopy sequence MEGA-PRESS, developed by CMRR, to evaluate the animal model-derived hypothesis that alterations in GABA and glutamate systems underlie cognitive and social impairments in NF1 53–55. MEGA-PRESS allows separation of GABA signals from stronger overlying signals of other metabolites 56.…”
Section: Methods and Analysismentioning
confidence: 99%